1994
DOI: 10.2307/2234673
|View full text |Cite
|
Sign up to set email alerts
|

UK Directors' Trading: The Impact of Dealings in Smaller Firms

Abstract: This paper reassesses the UK results of significant abnormal returns from directors' trading for a new sample of directors ' trades 1984-1986, and finds that abnormal returns tend to be concentrated in smaller firms. When an appropriate benchmark portfolio is used, it is found that the significance of the abnormal returns is substantially reduced, with the implication that directors' trading does not yield particularly high profits to either the directors themselves or to an outside investor mimicking those tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 14 publications
1
49
0
1
Order By: Relevance
“…We also include a set of control variables referring to company characteristics. First, since several studies (e.g., Seyhun 1986 andPurkis 1994) have shown that profits are higher for smaller firms, we define the variable SIZE, which equals the natural logarithm of the market value of a firm at the beginning of the respective calendar year, to control for the firm's size. Second, our results might be triggered by thinly traded stocks.…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…We also include a set of control variables referring to company characteristics. First, since several studies (e.g., Seyhun 1986 andPurkis 1994) have shown that profits are higher for smaller firms, we define the variable SIZE, which equals the natural logarithm of the market value of a firm at the beginning of the respective calendar year, to control for the firm's size. Second, our results might be triggered by thinly traded stocks.…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…This is true for early (see, e.g., Jaffe [1], Finnerty [2], or Seyhun [3]) and also recent U.S. studies (like, e.g., Lakonishok and Lee [4], Jeng et al [5], or Aktas et al [6]). Comparable results are also documented for some European markets, like the UK (see, e.g., Pope et al [7], Gregory et al [8], and more recently Calvo and Lasfer [9], or Fidrmuc et al [10]), the Netherlands (see Biesta et al [11] and Aktas et al [12]), or Spain (see Del Brio et al [13]). Eckbo and Smith [14] report zero or even negative abnormal returns for insider transaction in Norway.…”
mentioning
confidence: 65%
“…Seyhun (1986), Lin and Howe (1990), and Chang and Suk (1998) report positive abnormal returns on insider purchases for the case of the USA. King and Röell (1988), Pope et al (1990), Gregory et al (1994), and Gregory et al (1997) confirm the existence of positive abnormal returns for the UK over horizons of 6 to 12 months following directors' purchases. More recent studies by Friederich et al (2002) and Fidrmuc et al (2006) corroborate the findings of the previous studies for UK companies over the short term.…”
Section: Insider Tradingmentioning
confidence: 85%